2022
DOI: 10.1186/s12916-022-02467-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal mRNA signatures for the early diagnosis of clear cell renal cell carcinoma

Abstract: Background There are no proven tumor biomarkers for the early diagnosis of clear cell renal cell carcinoma (ccRCC) thus far. This study aimed to identify novel biomarkers of ccRCC based on exosomal mRNA (emRNA) profiling and develop emRNA-based signatures for the early detection of ccRCC. Methods Four hundred eighty-eight participants, including 226 localized ccRCCs, 73 patients with benign renal masses, and 189 healthy controls, were recruited. Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…For better prognosis prediction, a nomogram based on GHITM expression for KIRC was constructed to predict the 1‐, 3‐ and 5‐year survival rates of patients, and there was a good agreement between prediction and observation according to corresponding calibration curves (Figure 2C,D). A 5‐year survival rate of early RCC is over 90%, but no efficient biomarker was found for early diagnosis of KIRC over the past several decades 32 . GHITM diagnostic value in KIRC was evaluated using GEO and TCGA datasets.…”
Section: Resultsmentioning
confidence: 99%
“…For better prognosis prediction, a nomogram based on GHITM expression for KIRC was constructed to predict the 1‐, 3‐ and 5‐year survival rates of patients, and there was a good agreement between prediction and observation according to corresponding calibration curves (Figure 2C,D). A 5‐year survival rate of early RCC is over 90%, but no efficient biomarker was found for early diagnosis of KIRC over the past several decades 32 . GHITM diagnostic value in KIRC was evaluated using GEO and TCGA datasets.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the identification of subclasses of extracellular vesicles derived from cancer cells and microenvironmental components associated with well-defined pathological processes would allow them to serve as complementary biomarkers of circulating cfDNA and circulating tumor cells. In recent years, several studies have demonstrated the value of exosomes as cancer biomarkers, allowing longitudinal monitoring of tumor heterogeneity and early identification of cancer subtypes ( 154 , 155 ), as well as monitoring microenvironmental subversion ( 156 ), tumor progression and prognostic decisions ( 157 ), and response to therapy to tailor therapeutic interventions ( 158 , 159 ). Further developments in this field will bring us closer to the most important goal of providing personalized cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding functional exosomal mRNAs, an early study reported that exosomal mRNAs can complete translation in receptor cells [150]. Recently, exosomal mRNAs CUL9, KMT2D, PBRM1, PREX2 and SETD2 were found to be possible novel potential biomarkers for clear cell renal cell carcinoma (ccRCC) [151]. Studies on exosomal ncRNAs have focused on miRNAs, lncRNAs & circR-NAs.…”
Section: Nucleic Acidsmentioning
confidence: 99%